2019
DOI: 10.1101/598052
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EMT-induced cell mechanical changes enhance mitotic rounding strength

Abstract: To undergo mitosis successfully, most animal cells need to acquire a round shape to provide space for the mitotic spindle. This mitotic rounding relies on mechanical deformation of surrounding tissue and is driven by forces emanating from actomyosin contractility. Cancer cells are able to maintain successful mitosis in mechanically challenging environments such as the increasingly crowded environment of a growing tumor, thus, suggesting an enhanced ability of mitotic rounding in cancer. Here, we show that epit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 65 publications
(79 reference statements)
3
18
0
Order By: Relevance
“…Several recent studies by us and others have revealed that molecular changes that occur during oncogenesis can alter the ability of cells to apply force at mitosis. Work by Hosseini and colleagues reports that epithelial-mesenchymal transition (EMT), a phenotypic transformation commonly found in many epithelial-derived cancers and frequently associated with invasion and metastasis (Yang et al, 2020) alters the mechanical properties of the mitotic cortex and the ability of cells to round up in stiff 3D environments (Hosseini et al, 2019). The observed changes in cortex mechanics were associated with changes in RhoA and Rac1 activity induced by EMT (Hosseini et al, 2019).…”
Section: Mitotic Rounding and Stiffening In Diseased Tissuementioning
confidence: 99%
“…Several recent studies by us and others have revealed that molecular changes that occur during oncogenesis can alter the ability of cells to apply force at mitosis. Work by Hosseini and colleagues reports that epithelial-mesenchymal transition (EMT), a phenotypic transformation commonly found in many epithelial-derived cancers and frequently associated with invasion and metastasis (Yang et al, 2020) alters the mechanical properties of the mitotic cortex and the ability of cells to round up in stiff 3D environments (Hosseini et al, 2019). The observed changes in cortex mechanics were associated with changes in RhoA and Rac1 activity induced by EMT (Hosseini et al, 2019).…”
Section: Mitotic Rounding and Stiffening In Diseased Tissuementioning
confidence: 99%
“…EMT is commonly linked to early steps in metastasis promoting cell migration and cancer cell invasiveness [6][7][8][9]. Furthermore, EMT was shown to give rise to major changes in the molecular regulation of the actin cortex; the cytoskeletal regulator proteins RhoA and Rac1 undergo characteristic activity changes upon EMT indicating EMT-induced changes in the polymerisation process and the structure of the actin cytoskeleton [10][11][12][13]. While mechanical changes of cancer cells have been documented in many studies [10,[14][15][16][17][18][19][20], a detailed study of EMTinduced rheological changes of the actin cortex is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed that mitotic cells exhibit a large cell surface tension that ensures droplet-shaped cells in mechanical confinement. Using the previously developed analysis scheme for such droplet-shaped cells, we could determine cortical tension of measured cells from the corresponding AFM readout and cellular imaging 11,16 . We first investigated a HeLa cell line with a GFP-labeled construct of murine α-actinin-4 (Actn4-EGFP).…”
Section: Resultsmentioning
confidence: 99%
“…To increase fluorescence intensity, the aperture of the pinhole was set to 3 Airy units corresponding to an optical section thickness of 6 µm. Stationary state AFM forces were used to calculate cortical tension as described previously 11,16 . Briefly, as part of this analysis, cell height and cross-sectional area of the cell in the equatorial plane were used to estimate cell volume and other geometrical parameters (contact area, mean curvature) as described in 11 .…”
Section: Confocal Imaging In Combination With Afmmentioning
confidence: 99%